A correlation between Paco2 and body temperature in febrile patients. Issue 1 (January 1974) - Chapot, Gaston; Muller, Michèle; Barrault, Nicole; Dargnat, Nicole; Languillat, Jean-Michel
Abstract : Chapot, G., Muller, Michèle, Barrault, Nicole, Dargnat, Nicole, and Languillat, J-M. (1974). Thorax, 29, 104-105. A correlation between Pa co2 and body temperature in febrile patients. Paco2 has been measured in 49 patients with normal and raised body temperature. Within the temperature range 35·5°C-41·4°C, there was an inversely proportional relationship between Paco2 and body temperature with a highly significant correlation coefficient.